Childhood obesity-related cardiovascular risk factors and carotid intima-media thickness - Simşek, Enver; Balta, Hakan; Balta, Zeynep; Dallar, Yildiz (The Turkish Journal of Pediatrics, 2010)
The purpose of this study was to investigate the relationship between childhood obesity and carotid intima-media thickness (IMT). This is a cross-sectional study in obese children and non-obese control subjects. This study included 75 obese children and 40 non-obese control children. Systolic and diastolic blood pressure (SBP, DBP) values and waist and hip circumferences were measured. Fasting blood glucose and insulin concentrations, total cholesterol, triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were assayed. The carotid IMT was measured by high resolution B-mode ultrasonography. Waist/hip ratios, SBP and DBP were significantly increased in the obese group compared to the non-obese children (all p < 0.001). The total cholesterol, LDL-C, HDL-C, and TG in the obese children were significantly different from values in the control subjects (all p < 0.001). Compared to the controls, the obese children demonstrated significant differences in a number of clinical risk factors including body weight, body mass index (BMI), BMI-standard deviation score (SDS), SBP/DBP, waist circumference, hip circumference, and waist/hip ratio (all p < 0.001). Compared to the controls, the obese children showed increased mean carotid IMT values [0.52 mm (95% confidence interval [CI], 0.40-0.64 mm) vs. 0.35 mm (95% CI, 0.24-0.38 mm), p < 0.001]. Univariate correlation analysis revealed that the carotid IMT was closely related to the BMI-SDS, SBP/DBP, waist and hip circumferences, serum TG, cholesterol, LDL-C, HDL-C, fasting serum insulin level, and insulin resistance indices including the homeostasis model assessment of insulin resistance (HOMA-IR), fasting glucose-to-insulin ratio (FGIR), and quantitative insulin-sensitivity check index (QUICKI). Multiple regression analysis showed that the BMI-SDS, TG and QUICKI were independent predictive risk factors for increased carotid IMT. Measurements of BMI-SDS, blood pressure, waist and hip circumferences, serum TG levels, the QUICKI insulin resistance index, and carotid IMT by ultrasonography are suitable in pediatric patients in a clinical setting and may be used for screening of obese children.